2014
DOI: 10.1103/physrevb.90.125307
|View full text |Cite
|
Sign up to set email alerts
|

Superradiance and enhanced luminescence from ensembles of a few self-assembled quantum dots

Abstract: We study theoretically the evolution of photoluminescence (PL) from homogeneous and inhomogeneous ensembles of a few coupled QDs. We discuss the relation between signals from a given QD ensemble under strong and weak excitation (full inversion and linear response regimes): A system homogeneous enough to manifest superradiant emission when strongly inverted shows a non-exponential decay of the PL signal under spatially coherent weak excitation. In an inhomogeneous ensemble the PL decay is always nearly exponent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This scaling is considerably lower than that of the coherently driven three level systems (see (3.25),~N 8 ) and of course also the naive brute force solution (~3 N 2 ). Please bear in mind that this does not correspond to a Hilbert/ Liouville space truncation-we solely observed that some density matrix elements are not connected to the other elements and thus remain zero and we therefore do not need to compute them.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…This scaling is considerably lower than that of the coherently driven three level systems (see (3.25),~N 8 ) and of course also the naive brute force solution (~3 N 2 ). Please bear in mind that this does not correspond to a Hilbert/ Liouville space truncation-we solely observed that some density matrix elements are not connected to the other elements and thus remain zero and we therefore do not need to compute them.…”
mentioning
confidence: 71%
“…In quantum optics many two-level systems interacting with quantized electromagnetic/cavity modes are extensively studied in contexts as diverse as superradiance, entanglement, lasing, nonclassical light generation, higher harmonic generation, quantum phase transitions and quantum information processing [1][2][3][4][5][6][7][8][9][10]. Such model systems were recently also applied in the context of quantum plasmonics [11], especially in the context of spasers [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectral tunability so that QDs emit indistinguishable photons is required in quantum repeaters and distributed quantum networks [1][2][3]. The tunability of mutual resonance of QDs can also be utilized in quantumtunneling-based [4] or energy-transfer-based devices [5], as well as in the manifestation and application of the superradiance mechanism [6][7][8][9]. Spectral matching with a specific cavity mode [10] has also been pursued for photon-emitting devices with high extraction efficiency in terms of the spontaneous emission rate and radiation pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced spontaneous emission can also occur due to strong correlations between quantum dots immersed in confining potentials [10]. More broadly, theoretical and experimental studies of superradiance in condensed-matter have led to reexamination of collective effects in nanoscale systems [11,12], metallic nanoparticles and nanostructures [13,14], and magnetic nanosystems, as well [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%